2019
DOI: 10.7554/elife.47391
|View full text |Cite
|
Sign up to set email alerts
|

Distinct subdivisions of human medial parietal cortex support recollection of people and places

Abstract: Human medial parietal cortex (MPC) is implicated in multiple cognitive processes including memory recall, visual scene processing and navigation, and is a core component of the default mode network. Here, we demonstrate distinct subdivisions of MPC that are selectively recruited during memory recall of either specific people or places. First, distinct regions of MPC exhibited differential functional connectivity with medial and lateral regions of ventral temporal cortex (VTC). Second, these same medial regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
122
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(153 citation statements)
references
References 75 publications
(141 reference statements)
30
122
1
Order By: Relevance
“…The distinct task activation patterns along the posterior midline are consistent with results from two recent studies that found similar differential activity within subjects (tasked with making judgments about either people or scenes; e.g., see Fig. 1 in Peer et al 2015; see also Silson et al 2019). The current results support that such task activation differences within canonical DN regions are well-predicted by the hypothesis of separation between two distributed networks, labeled Networks A and B, and are not limited to specific cortical zones.…”
Section: Parallel Distributed Network With Adjacent Regions Across Tsupporting
confidence: 90%
See 1 more Smart Citation
“…The distinct task activation patterns along the posterior midline are consistent with results from two recent studies that found similar differential activity within subjects (tasked with making judgments about either people or scenes; e.g., see Fig. 1 in Peer et al 2015; see also Silson et al 2019). The current results support that such task activation differences within canonical DN regions are well-predicted by the hypothesis of separation between two distributed networks, labeled Networks A and B, and are not limited to specific cortical zones.…”
Section: Parallel Distributed Network With Adjacent Regions Across Tsupporting
confidence: 90%
“…Second, the anatomical dissociations within individuals include regions along the anterior and posterior midline that were previously proposed as part of the DN "core" due to their participation in multiple task domains. The network organization as revealed within the individual, as well as findings from task-based activation patterns along the posterior midline within individuals (Peer et al 2015;Silson et al 2019), suggest that these zones may possess spatially separate functional regions. Altogether, these results raise the possibility that there may be broad functional specialization of the widely distributed networks, rather than local subzones of specialization that converge on core hubs.…”
Section: Introductionmentioning
confidence: 83%
“…Our previous study identified a division between posterior parietal regions preferentially active for spatial processing and more anterior regions preferentially active for social processing (Peer et al, 2015). This finding was recently replicated and extended by another study that used recall of people and places and found the same posterior-anterior division between spatial and social processing (Silson et al, 2019a). In addition, comparison of scene viewing to other categories identifies the posterior region, retrosplenial complex, as scene-selective (Epstein, 2008;Epstein and Higgins, 2007;Silson et al, 2016Silson et al, , 2019b.…”
Section: Discussionsupporting
confidence: 63%
“…On the one hand, mechanistic accounts of perceptual memory often posit that explicit recall of visual stimuli reinstates perceptual representations in visual areas, including the three areas of the scene-perception network (parahippocampal place area (PPA), occipital place area (OPA), and medial place area (MPA)) [17][18][19][20] . However, recent studies have found that memory-based representations are not strictly colocalized with perceptual representations, but instead that information may transition from perceptual to memory-based representations moving anteriorly from areas of the sceneperception network 1,[21][22][23][24] . Resolving this discrepancy is critical to understanding how contextual information from memory is brought to bear on visual representations in the brain.…”
mentioning
confidence: 99%